Pengaruh Model Pembelajaran Kooperatif dan Perilaku Berkarakter Terhadap Kemampuan Pemecahan Masalah Matematika Dengan Memperhitungkan Kovariat Disposisi Matematis Siswa SMA - Supratman Supratman (Universitas Mathla'ul Anwar Banten, 2015)
This study discusses about mathematical problem solving ability of sudents of SMA Negeri 1 Wundulako, Souteast Sulawesi province. Discussion is done by descriptive and inferential analysis to reveal mathematical problem solving ability of sudents after being taught by cooperative learning model. Results of statistical analysis of the data concluded that the mathematical problem solving ability of students of SMAN 1 Wundulako based on three aspects classified in a good category, but these three aspects have different average. From those three aspects, the average of students are low at problem solving aspect namely choosing and applying strategy to solve model or mathematical problem and out of mathematical problem. However, the learning spirit of students is incrieasing enough when taught with cooperative learning model, of Jigsaw and TSTS types. This condition causes average of mathematical problem solving ability of students which taught with cooperative learning model, Jigsaw type is better than TSTS type or STAD. While inferentially concluded that there is an interaction between cooperative learning model and character behavior of the mathematical problem solving ability.